A Full MALDI-Based Approach to Detect Plasmid-Encoded KPC-Producing Klebsiella pneumoniae - Cordovana, Miriam; Kostrzewa, Markus; Glandorf, Jörg; Bienia, Michael; Ambretti, Simone; Pranada, Arthur B. (Frontiers in Microbiology, 2018)
KPC-producing Klebsiella pneumoniae represent a severe public health concern worldwide. The rapid detection of these isolates is of fundamental importance for the adoption of proper antibiotic treatment and infection control measures, and new applications of MALDI-TOF MS technology fit this purpose. In this study, we present a full MALDI-based approach to detect KPC-producing strains, accomplished by the automated detection of a KPC-specific peak (at 11,109 m/z) by a specific algorithm integrated into the MALDI Biotyper system (Bruker Daltonik), and the confirmation of carbapenemase activity by STAR-Carba imipenem hydrolysis assay. A total of 6209 K. pneumoniae isolates from Italy and Germany were investigated for the presence of the KPC-related peak, and a subset of them (n=243) underwent confirmation of carbapenemase activity by STAR-Carba assay. The novel approach was further applied directly to positive blood culture bottles (n=204), using the bacterial pellet obtained with Sepsityper kit (Bruker Daltonik). The novel approach enabled a reliable and very fast detection of plasmid-encoded KPC-producing K. pneumoniae strains, from colonies as well as directly from positive blood cultures. The automated peak detection enabled the instant detection of KPC bearing K. pneumoniae during the routine identification process, with absolute specificity and a good sensitivity (85.1 %). The sensitivity is likely mainly related to the prevalence of the specific plasmid harboring clones among all the KPC-producing circulating strains. STAR-Carba carbapenemase confirmation showed 100% sensitivity and specificity.